Efektivitas Kebijakan Moneter Nonkonvensional: Bukti dari Jalur Pinjaman Bank di Indonesia - samsul arifin arifin; sayifullah sayifullah (Jurnal Ekonomi Pembangunan, 2022)
This study analyzes the effectiveness of quantitative easing as a stimulus for bank lending in Indonesia and examines credit performance which is influenced by assets, capital and the risk of bad loans. This paper uses a balanced panel data regression model, exploring effects including individual and time fixed effects. The use of GMM to overcome bias due to the use of the dependent variable lag uses bank level data from 2020q1 to 2022q1. The results show that monetary policy is ineffective during the COVID-19 pandemic and the performance of bank lending has a downward trend. The results of the study highlight the ineffectiveness of monetary policy as indicated by a higher bank liquidity ratio which in fact has a tendency to create lower bank credit growth. The factors that determine the amount of credit are bank assets and capital. This paper contributes to the literature by investigating the effectiveness of quantitative easing as a stimulus for bank lending in Indonesia using firm-level data.